Toward Organizational Behavior - Cummings, L. L. (Academy of Management Review, 1978)
Three bases are analyzed for partitioning organizational behavior (OB) as a field of inquiry from other related fields. OB is characterized by three dimensions and three themes that impact the articulation of these dimensions in teaching, research, and application. Implications are drawn for the evolution of OB as an enacted discipline.